Nab-Sirolimus for Patients With Malignant Perivascular Epithelioid Cell Tumors. Issue 33 (20th November 2021) - Wagner, Andrew J.; Ravi, Vinod; Riedel, Richard F.; Ganjoo, Kristen; Van Tine, Brian A.; Chugh, Rashmi; Cranmer, Lee; Gordon, Erlinda M.; Hornick, Jason L.; Du, Heng; Grigorian, Berta; Schmid, Anita N.; et al.
Abstract : PURPOSE: Malignant perivascular epithelioid cell tumor (PEComa) is a rare aggressive sarcoma, with no approved treatment. To our knowledge, this phase II, single-arm, registration trial is the first prospective clinical trial in this disease, investigating the safety and efficacy of the mammalian target of rapamycin inhibitor nab -sirolimus (AMPECT, NCT02494570 ). PATIENTS AND METHODS: Patients with malignant PEComa were treated with nab -sirolimus 100 mg/m 2 intravenously once weekly for 2 weeks in 3-week cycles. The primary end point was objective response rate evaluated by independent radiology review. Key secondary end points included duration of response, progression-free survival, and safety. A key exploratory end point was tumor biomarker analysis. RESULTS: Thirty-four patients were treated (safety evaluable), and 31 were evaluable for efficacy. The overall response rate was 39% (12 of 31; 95% CI, 22 to 58) with one complete and 11 partial responses, 52% (16 of 31) of patients had stable disease, and 10% (3 of 31) had progressive disease. Responses were of rapid onset (67% by week 6) and durable. Median duration of response was not reached after a median follow-up for response of 2.5 years, with 7 of 12 responders with treatment ongoing (range, 5.6-47.2+ months). Twenty-five of 31 patients had tumor mutation profiling: 8 of 9 (89%) patients with a TSC2 mutation achieved a confirmed response versus 2 of 16 (13%) without TSC2 mutation ( P < .001). The median progression-free survival was 10.6 months (95% CI, 5.5 months to not reached), and the median overall survival was 40.8 months (95% CI, 22.2 months to not reached). Most treatment-related adverse events were grade 1 or 2 and were manageable for long-term treatment. No grade ≥ 4 treatment-related events occurred. CONCLUSION: nab -Sirolimus is active in patients with malignant PEComa. The response rate, durability of response, disease control rate, and safety profile support that nab -sirolimus represents an important new treatment option for this disease. Abstract :